Proceedings of the 58th Annual Meeting of the Association for Computational Linguistics 2020
DOI: 10.18653/v1/2020.acl-main.407
|View full text |Cite
|
Sign up to set email alerts
|

Compositionality and Generalization In Emergent Languages

Abstract: Natural language allows us to refer to novel composite concepts by combining expressions denoting their parts according to systematic rules, a property known as compositionality. In this paper, we study whether the language emerging in deep multi-agent simulations possesses a similar ability to refer to novel primitive combinations, and whether it accomplishes this feat by strategies akin to human-language compositionality. Equipped with new ways to measure compositionality in emergent languages inspired by di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(103 citation statements)
references
References 25 publications
6
94
1
Order By: Relevance
“…Our concern is illustrated by the recent findings of Chaabouni et al (2020), who observed that the degree of compositionality of emergent languages is not correlated with the generalization capabilities of the agents that rely on them to solve a task. Indeed, lacking any specific pressure towards developing a (naïvely) compositional language, their agents were perfectly capable of developing generalizable but non-compositional communication systems.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Our concern is illustrated by the recent findings of Chaabouni et al (2020), who observed that the degree of compositionality of emergent languages is not correlated with the generalization capabilities of the agents that rely on them to solve a task. Indeed, lacking any specific pressure towards developing a (naïvely) compositional language, their agents were perfectly capable of developing generalizable but non-compositional communication systems.…”
Section: Discussionmentioning
confidence: 92%
“…Havrylov and Titov (2017) looked for symbol-position combina-tions that encode a single concept in an image, as a sign of a compositional behavior. A naïvely compositional language will maximize the two recently proposed compositionality measures of residual entropy (Resnick et al, 2019) and positional disentanglement (Chaabouni et al, 2020).…”
Section: Operationalizing Compositionalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Collaborative games have long served as a testbed for studying language (Werner and Dyer, 1991) and emergent communication (Schlangen, 2019a;Lazaridou et al, 2018;Chaabouni et al, 2020). Suhr et al (2019a) introduced an environment for evaluating language understanding in the service of a shared goal, and Andreas and Klein (2016) use a visual paradigm for studying pragmatics.…”
Section: By Yourself Ws4 ⊂ Ws5mentioning
confidence: 99%
“…To facilitate such interaction, neural networks' emergent language should possess many natural-language-like properties. However, it has been shown that, even if these emergent languages lead to successful communication, they often do not bear core properties of natural language (Kottur et al, 2017;Bouchacourt and Baroni, 2018;Lazaridou et al, 2018;Chaabouni et al, 2020).…”
Section: Introductionmentioning
confidence: 99%